Presence and Absence of Muscle Contraction Elicited by Peripheral Nerve Electrical Stimulation Differentially Modulate Primary Motor Cortex Excitability - Sasaki, Ryoki; Kotan, Shinichi; Nakagawa, Masaki; Miyaguchi, Shota; Kojima, Sho; Saito, Kei; Inukai, Yasuto; Onishi, Hideaki (Frontiers in Human Neuroscience, 2017)
Modulation of cortical excitability by sensory inputs is a critical component of sensorimotor integration. Sensory afferents, including muscle and joint afferents, to somatosensory cortex (S1) modulate primary motor cortex (M1) excitability, but the effects of muscle and joint afferents specifically activated by muscle contraction are unknown. We compared motor evoked potentials (MEPs) following median nerve stimulation (MNS) above and below the contraction threshold based on the persistence of M-waves. Peripheral nerve electrical stimulation (PES) conditions, including right MNS at the wrist at 110% motor threshold (MT; 110% MNS condition), right MNS at the index finger [sensory digit nerve stimulation (DNS)] with stimulus intensity approximately 110% MNS (DNS condition), and right MNS at the wrist at 90% MT (90% MNS condition) were applied. PES was administered in a 4 s ON and 6 s OFF cycle for 20 min at 30 Hz. In experiment 1 (n = 15), MEPs were recorded from the right abductor pollicis brevis (APB) before (baseline) and after PES. In experiment 2 (n = 15), M- and F-waves were recorded from the right APB. Stimulation at 110% MNS at the wrist evoking muscle contraction increased MEP amplitudes after PES compared with those at baseline, whereas DNS at the index finger and 90% MNS at the wrist not evoking muscle contraction decreased MEP amplitudes after PES. M- and F-waves, which reflect spinal cord or muscular and neuromuscular junctions, did not change following PES. These results suggest that muscle contraction and concomitant muscle/joint afferent inputs specifically enhance M1 excitability.